Adaptive capacity of high- and low dyke farmers to hydrological changes in the Vietnamese Mekong delta - Hoang, Long Phi (2023)
This research assesses the adaptive capacity of farmers in the Vietnamese Mekong Delta's floodplains (VMD) with respect to hydrological changes. Currently, climate change and socio-economic developments induce extreme- and diminishing floods, which in turn increase farmers' vulnerability. This research assesses farmers' adaptive capacity to hydrological changes using two prevalent farming systems: high dykes featuring triple-crop rice farming and low dykes where fields are left fallow during the flood season. We examine (1) farmers' perceptions on a changing flood regime and their current vulnerabilities and (2) farmers' adaptive capacity through five sustainability capitals. Methods include a literature review and qualitative interviews with farmers. Results show that extreme floods are becoming less frequent and damaging, depending on arrival time, depth, residence time, and flow velocity. In extreme floods, farmers' adaptive capacity is generally strong, and only low dyke farmers experience damage. As for diminishing floods, which is an emerging phenomenon, the overall adaptive capacity of farmers is remarkably weaker and varies between high- and low dyke farmers. Financial capital is lower for low dyke farmers due to their double-crop rice system, and natural capital is low for both farmer groups due to a decrease in soil- and water quality, affecting yields and increasing investment costs. Farmers also struggle with an unstable rice market due to strong fluctuating prices for seeds, fertilizers, and other inputs. We conclude that both high- and low dyke farmers have to cope with new challenges, including fluctuating flood patterns and the depletion of natural resources. Increasing farmers resilience should focus on exploring better crop varieties, adjusting crop calendars, and shifting to less water-intensive crops.